2020
DOI: 10.1099/ijsem.0.004293
|View full text |Cite
|
Sign up to set email alerts
|

Genomic-based taxonomic classification of the family Erythrobacteraceae

Abstract: The family Erythrobacteraceae , belonging to the order Sphingomonadales , class Alphaproteobacteria , is globally distributed in various environments. Currently, this family consist of seven genera: Alterery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 332 publications
(125 citation statements)
references
References 130 publications
9
106
0
Order By: Relevance
“…However, an AAI range of 60–80 % was observed in phylogenetically distinct but related genera [24] and phylogenies based on 16S rRNA gene sequences were complemented with core genome phylogenies to delineate higher taxonomic ranks [20]. More recently, OGRI metrics were successfully used to delineate genera within the families Erythrobacteracae , Lactobacillaceae , Leuconostocaceae and Rhodobacteraceae [29–31]. In the study conducted on the Erythrobacteraceae , cut-offs of 60–80 % AAI and 50 % percentage of conserved proteins (POCP) were used for genus-level delineations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an AAI range of 60–80 % was observed in phylogenetically distinct but related genera [24] and phylogenies based on 16S rRNA gene sequences were complemented with core genome phylogenies to delineate higher taxonomic ranks [20]. More recently, OGRI metrics were successfully used to delineate genera within the families Erythrobacteracae , Lactobacillaceae , Leuconostocaceae and Rhodobacteraceae [29–31]. In the study conducted on the Erythrobacteraceae , cut-offs of 60–80 % AAI and 50 % percentage of conserved proteins (POCP) were used for genus-level delineations.…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted on the Erythrobacteraceae , cut-offs of 60–80 % AAI and 50 % percentage of conserved proteins (POCP) were used for genus-level delineations. In particular, they observed that AAI and evolutionary distance were strongly correlated [29]. In the analysis of the Lactobacillaceae and Leuconostocaceae families, the proposal of the novel genera was based on the following criteria: novel genera must represent monophyletic clades, possess rational AAI values both within and between genera, and exhibit some degree of phenotypic uniformity [30].…”
Section: Introductionmentioning
confidence: 99%
“…The DNA G+C content of strain Ery12 T was 60.9 %, a value in the range reported for members of the genus Tsuneonella , i.e. 60.5–67.0 % [1].…”
Section: Genome Featuresmentioning
confidence: 90%
“…The genus Tsuneonella belonging to the family Erythrobacteraceae , was proposed by Xu et al . [1]. At the time of writing, the genus Tsuneonella comprised of seven species with validly published names.…”
Section: Full-textmentioning
confidence: 99%
“…However, not all of those species possess photosystem-II photosynthetic apparatus, hence not all of them belong to AAP bacteria. Species such as Roseobacter ponti , Roseobacter cerasinus (Muramatsu et al 2020), Erythrobacter aquimixticola (Park et al 2017), Erythrobacter arachoides (Xing et al 2017), Erythrobacter insulae (Park et al 2020) and Erythrobacter atlanticus (Zhuang et al 2015) are several species from both genera which do not possess phototrophic trait and hence are suggester for genera reclassification (Hördt et al 2020;Xu et al 2020) The ecological role of marine AAP bacteria was not really known until 2000, when it was discovered that photoheterotrophic ability might contribute to their survival in nutrient-poor marine environments, such as open ocean (Kolber et al 2000;Kirchman 2018). Marine AAP bacteria abundance was firstly reported in 2001 where it contributes to 10% of total bacterioplankton in Pacific Ocean, implying its significant contribution towards global carbon cycle (Kolber et al 2001;Ritchie and Johnson 2012).…”
Section: Introductionmentioning
confidence: 99%